Tannin Concentration of Gyrinops Tea Taken Form Different Agarwood Plantation and Different Processing Method. Issue 1 (November 2021) - Wangiyana, I G A S; Supriadi,; Nikmatullah, A; Sunarpi,; Mulyaningsih, L
Abstract: Tannin is one of the essential components that determine the quality of herbal tea products. This research aims to conduct a quantitative tannin assay of Gyrinops tea with different leaf sampling locations and processing methods. Factorial Completely Randomized Design was used as an experimental design with two treatment factors. The first factor is sampling location (Kekait, Lingsar, and Pejaring). The second factor is the processing method (Fresh leaves and Dried leaves). A titrimetric method with KMnO4 and Indigo carmine reagent was used for quantitative tannin measurement. ANOVA and DMRT at a 5% significant level were used for tannin concentration analysis. The result indicated that the first, second, and interaction factors significantly affected tannin concentration. Drying the G. versteegii leaves could increase the tannin concentration of the Gyrinops tea product. G. versteegii leaves taken from Kekait have shown highest tannin concentration among other regions. It could be concluded that dried G. versteegii leaves Kekait could produce Gyrinops tea with high quality based on tannin concentration measurement.